Huntington's disease in Grampian region: correlation of the CAG repeat number and the age of onset of the disease. Issue 12 (December 1993) - Simpson, S A; Davidson, M J; Barron, L H
Abstract : The identification of an unstable trinucleotide repeat as the mutation responsible for Huntington's disease (HD) has given the hope that additional information can be provided about age of onset and mode of action of the mutated gene. We present in this paper results of a clinical and molecular study of 82 patients affected with HD from 46 pedigrees within the Grampian region, Scotland. Our results show a correlation between age of onset and size of the CAG expansion. This study has produced no overlap in mutation size between affected and unaffected alleles. The sex of the parent transmitting the mutated allele and the size of the normal allele have no significant effect on the clinical features of the disease. In the three juvenile cases the affected parent was the father but the number of cases is too small to produce statistical significance. An increase in the CAG repeat size is shown in the transmission of the gene in five cases, accompanied by an earlier age of onset in four; in three of these cases, the affected parent was the father. Eleven sib pairs were studied and there is a negative correlation between the difference in age at onset and the difference in repeat size. Thus there is some evidence of a relationship, but this is not statistically significant because of the small numbers involved. The presence of the same or different normal allele had no effect on age of onset in this small group. We suggest that additional factors, as yet unrecognised, influence the age of onset and clinical presentation of HD.